Bacterial wilt pathogen induced spatial shifts of root-associated microbiome and metabolome of potatoes - Lai, Xianjun; He, Zhouhua; Wang, Shuyan; Zhang, Feng; Wang, Haiyan; Wang, Xiyao; Liu, Shifeng; Yan, Lang (Frontiers in Plant Science, 2025)
IntroductionPlant root-associated microbiomes play an important role in plant health, yet their responses to bacterial wilt remain unclear poorly understood.MethodsThis study investigated spatial variations in microbiome and metabolome composition across three root-associated niches—root-surrounding soil, rhizosphere, and endosphere—of healthy and Ralstonia solanacearum-infected potato plants. A total of 36 samples were analyzed, with microbial diversity assessed by full-length 16S rRNA and ITS sequencing, and metabolic profiles characterized using LC-QTOF-MS.ResultsAlpha diversity analysis revealed that bacterial diversity in healthy plants was consistently higher than in diseased plants, progressively increasing from the root-surrounding soil to the rhizosphere, and most notably in the endosphere, where the Shannon index declined from 5.3 (healthy) to 1.2 (diseased). In contrast, fungal diversity was lower in diseased plants in the root-surrounding soil and rhizosphere, but significantly elevated in the endosphere, suggesting niche-specific microbial responses to pathogen stress. Beta diversity confirmed significant microbiome restructuring under pathogen stress (R² > 0.5, p = 0.001). Taxonomic analysis showed over 98% dominance of Proteobacteria in the diseased endosphere, where Burkholderia, Pseudomonas, and Massilia enriched in healthy plants were significantly reduced. R. solanacearum infection promotes the enrichment of Fusarium species in both the rhizosphere and endosphere. Metabolomic analysis revealed extensive pathogen-induced metabolic reprogramming, with 299 upregulated and 483 downregulated metabolites in the diseased endosphere, including antimicrobial metabolites such as verruculogen and aurachin A. Network analysis identified XTP as a central metabolite regulating microbial interactions, whereas antimicrobial metabolites exhibited targeted pathogen suppression. O2PLS analysis revealed that pathogen-induced antimicrobial metabolites (e.g., Gentamicin X2, Glutathionylspermine) were associated with Clostridia and Ketobacter in diseased plants, while nucleotide-related compounds (e.g., XTP) correlated with Rhodomicrobium and others, indicating infection-driven microbial adaptation and metabolic restructuring.DiscussionThese findings provide insights into pathogen-driven disruptions in root microbiomes and suggest potential microbiome engineering strategies for bacterial wilt management.